Effect of gypsum and potassium fertilisation on the nutritive value of legume-grass mixture - Waldemar Zielewicz; Barbara Wróbel (Plant, Soil and Environment)
The four-year field trial was conducted at the Rolnicze Gospodarstwo Doświadczalne Brody (Brody Experimental Farm), Poznań University of Life Sciences, Poland. This study aimed to assess how different doses of gypsum and potassium (K) fertilisers influenced the nutritive value of the alfalfa-grass mixture. The following two experimental factors were duplicated: gypsum fertilisation - two levels (0 and 500 kg/ha) and K fertilisation - four levels (0, 30, 60, and 120 kg/ha). The sward was harvested three times at the full budding phase of alfalfa. The content of nutritive components: crude protein (CP), crude fibre (CF), crude ash (CA) and water-soluble sugars (WSC) by NIRS technique was assessed. The combined application of gypsum and K significantly increased the yields obtained only in the 1st and 3rd harvests of the sward. In the case of CP and WSC, the application of gypsum and K showed no significant effect on the content of these components in the sward. At the same time, it significantly influenced the higher content of CF and CA only in the case of the 2nd harvest. Analysing the influence of only the effect of K on the results obtained, a response of increasing CF content in the sward under the influence of increasing doses of this nutrient was noted. The average potassium content of the sward increased from a K0 fertilisation level to an application rate of K60. In the case of CA content, there was a successive increase with the application of successive fertilisation rates from K0 to a rate of K120. Based on the average yield results, a similar response was observed for the increase in yields obtained with increasing potassium fertilisation rates from K0 to K120. CP content increased due to gypsum fertilisation, as did the achieved sward yields of the alfalfa-grass mixture. The biomass of the alfalfa-grass mixture without gypsum fertilisation contained more WSC than the fertilised one.